(untitled) (Journal of Parents and Teachers, 2014)
Technology has invaded many people’s homes. In this article the author focuses especially on television, highlighting that the time that children are affected by this screen is very high. The author proposes a list of alternatives that children can make instead of being in front of television: going outside, reading, listening to music, playing sports ..., and saying that, without a doubt, the absence of this type of activities affected to the cognitive, affective, social and physical development of the child.